Going for silver-senior consumers’ reviews of medical tourism - Rodrigues, H.; Brochado, A. (New techniques for brand management in the healthcare sector, 2021)
Senior medical tourism is a growing niche market. Senior citizens are increasingly traveling abroad with the stated intent of accessing medical treatment. This study sought to identify the main dimensions of overall experiences in senior medical tourism. Data based on senior citizens’ comments and ratings were retrieved from the treatment abroad website, with a focus on customers over 54 years old. Content analyses identified eight major themes in medical tourism reviewers. The themes of happiness (with the results) and treatment are predominant in senior consumers. The results are relevant to managers and marketing researchers who run medical tourism businesses, providing them with a deeper understanding of the senior market on services and identifying which services’ quality most significantly influence customers’ recommendations.